A Decade-Long Retrospective Study of Factors Influencing Survival in Ruptured Abdominal Aortic Aneurysm - Kalender, Günay; Weissmann, Thomas; Dinç, Ugur (Journal of Clinical Medicine, 2024)
Background: Ruptured abdominal aortic aneurysm (rAAA) carries a high mortality risk, requiring rapid diagnosis and intervention. This study assesses various clinical factors influencing rAAA management outcomes in alignment with evolving guidelines from 2011 to 2024. Methods: A retrospective analysis of 62 rAAA patients treated at Vivantes Clinic, Berlin, from July 2014 to May 2024 was conducted. Data were obtained from medical records, focusing on vital parameters at admission and during treatment. Both numerical and categorical variables were analyzed to identify survival determinants. Results: The overall survival rate was 55%. Significant differences in systolic and diastolic blood pressures during surgery were noted between survivors and non-survivors, with lower pressures observed in non-survivors at critical surgical stages. Other vital signs showed no significant variations. Survival was significantly associated with gender, fluid therapy, and aneurysm location. Conclusions: Effective blood pressure management during surgery is crucial for improving survival in rAAA cases. This study emphasizes adherence to current clinical guidelines and highlights the need for ongoing research to fill existing knowledge gaps. Further investigations are essential to enhance patient care and outcomes in rAAA.
CRIS-Team Scopus Importer:2024-11-15
Keywords: abdominal aortic aneurysm; aortic rupture; controlled hypotension; operative surgical procedures